AICCRA Zambia Beneficiary Report: increasing smallholder farmers' access to enhanced climate information services and/or validate climate-smart agriculture - Kakwasha, Keagan; Jacobs-Mata, Inga; Mudege, Netsayi N.; Siamudaala, Victor; Dahl, Hauke (Accelerating Impacts of CGIAR Climate Research for Africa, 2022)
AICCRA Zambia partnered with agribusiness-based small and medium enterprises (SMEs) to increase access to climate information services for over 300,000 farmers negatively impacted by the effects of climate change. This partnership has resulted in 118,746 (36% women) smallholder farmers accessing and adopting climate smart agriculture technologies in the following agriculture value chains: off-grid solar irrigation; integrated aquaculture agriculture system; climate-smart seed varieties; and integrated mixed chicken/goats–legume systems